Solar water level controller - Lim, Min Siang (2010)
In today's society, the remote area is experiencing a great demand for supplied of water which beyond the reach of power lines. Sunlight, as the keys to a new generation of power sources are widely available for replace the conventional fuel resources. Hence the aim for this project is to module a solar water level controller pump to obtain the water from well or underground water source for the purpose of irrigate crops, water livestock, and provide potable drinking water. This project calculated and estimated the amount of water delivered depends on distance that water is lifted, distance traveled through a delivery pipe, the efficiency of the pump and the amount of energy needed as the main consideration. With this solar water controller, the remote area residents can enjoy the benefit from the solar energy as the lowest cost and sustainable alternative option with environmental friendly that are not polluting.